Standard specification for General Requirements for Flat-Rolled Stainless and Heat-Resisting Steel Plate, Sheet, and Strip (American Society of Testing Materials, 2010)
This specification covers a group of general requirements that, unless otherwise specified in the purchase order or in an individual specification, shall apply to rolled steel plate, sheet, and strip, under each of the following specifications issued by ASTM: Specifications A167, A176, A240/A240M, A263, A264, A265, A666, A693, A793, and A895.